Lia Eden Community and the New Religious Movement: Analysis of Social Psychology and Rational Choice Theory - Mohammad Takdir; Nuzulul Khair (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
This study aims to explain the emergence of the Lia Eden community as a new religious movement in Indonesia. This study also revealed the motivation of people to join the Lia Eden community, which was mostly attended by urban and educated people. This study used qualitative methods to answer the psychological symptoms of the emergence of the Lia Eden community. This study uses a case study on one of the contemporary religious movements in Indonesia, namely the Lia Eden movement. This type of study is in the form of literature or library research by tracing various studies in the form of books, journals, and research reports that are directly related to the emergence of Lia Eden and people’s interest in this movement. The approach used in this research is social psychology and the rational choice theory. This research shows that the emergence of the Lia Eden community is due to the disappointment of the organized religion existence which is considered unable to overcome the modern humanity crisis. From the disappointment was culminated in the organized religion existence, the Lia Eden community influenced everyone to follow this community. They want to achieve peace, harmony, and to treat the spiritual crisis that plagued their lives